2014
DOI: 10.1007/s12020-014-0373-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GLP-1 receptor agonists on waist circumference among type 2 diabetes patients: a systematic review and network meta-analysis

Abstract: Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are increasingly used in patients with type 2 diabetes. However, the effect on abdominal obesity has not yet been confirmed. The study aimed to systematically evaluate the effect of GLP-1RAs on waist circumference in patients with type 2 diabetes. MEDLINE, EMBASE, the Cochrane library and www.clinicaltrialgov were searched through October 31, 2013. Randomized controlled trials with available data were selected if they compared GLP-1 RAs with placebo and trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Weight loss in the Salba-chia group was accompanied by reductions of 3.5cm in waist 253 circumference, which is greater than that seen with different types of GLP-1 receptor agonists of 254 -1.85cm in comparison with placebo or insulin treatment(17). Although there was no difference .9%, P=0.047) from baseline in the Salba-chia group, but not in control,257 supporting the assumption that there was an attenuation in visceral fat.…”
mentioning
confidence: 79%
“…Weight loss in the Salba-chia group was accompanied by reductions of 3.5cm in waist 253 circumference, which is greater than that seen with different types of GLP-1 receptor agonists of 254 -1.85cm in comparison with placebo or insulin treatment(17). Although there was no difference .9%, P=0.047) from baseline in the Salba-chia group, but not in control,257 supporting the assumption that there was an attenuation in visceral fat.…”
mentioning
confidence: 79%
“…Several studies have shown that liraglutide has a positive effect on anthropometric parameters, in particular on body weight (as seen in the LEAD [Liraglutide Effect and Action in Diabetes] studies (reviewed in [3]) and waist circumference [15]. Liraglutide’s benefit was noted even in non-diabetic subjects [2, 8] and in those at high CV risk [16].…”
Section: Discussionmentioning
confidence: 99%
“…Alogliptin decreased fasting TG, apoB-48, and remnant-like particles (28), and anagliptin reduced fasting TG, apoB, and LDL-C (29). These effects may be related to the efficacy of these therapies in improving glycemic control with both GLP-1R agonists and DPP-4 inhibitors (12,30,31) and in reducing weight that is more notable with GLP-1R agonists than DPP-4 inhibitors (12,32,33). Future studies are required to determine the contribution of weight loss and improved glycemic control to fasting and postprandial lipids and to delineate the effects of these compounds on lipids independent of improved glycemic control and weight loss.…”
Section: Glp-1r Agonists Improve Fasting and Postprandial Lipid Profimentioning
confidence: 98%